Comparative study on different energy-saving plans using water-side economizer to retrofit the computer room air conditioning system. (15th June 2023) - Zou, Sikai; Zhang, Quan; Yue, Chang
Abstract: An energy efficient, environmentally friendly and economical retrofit plan of traditional computer room air conditioning system is necessary to reduce energy consumption of data centers. In this study, two energy-saving retrofit plans, a computer room air handler system with water-side economizer (Plan 1) and a loop thermosyphon system with water-side economizer (Plan 2), are compared with an air-cooled computer room air conditioning system (existing cooling system) in a data center. To analyze and compare the energy efficiency, environmental and economic potential, energy models of the existing cooling system and retrofit plans are established. Under different set points (including supply chilled water temperature and supply air temperature) and 2.08–6 kW average electric power of racks, the free cooling periods of Plan 1 and Plan 2 reach 3878–5867 h and 4541–7661 h, respectively, which lead to the annual energy consumption of Plan 1 and Plan 2 decreases by 27.6–47.3% and 53.4–63.6%, respectively. Due to the lower annual energy consumption of main equipment (including chillers, chilled water pumps, cooling water pumps and terminal equipment), Power Usage Effectiveness of Plan 2 is 0.049–0.090 lower than that of Plan 1, and Global Coefficient of Performance of Plan 2 is 23.3–67.3% higher than that of Plan 1. Furthermore, the annual CO2 emissions of Plan 1 and Plan 2 are 337.3–557.1 tons and 599.8–1106.9 tons less than those of the existing cooling system at different operating stages respectively. Finally, the dynamic payback periods of Plan 1 and Plan 2 are 4.11–5.42 years and 1.64–3.57 years. Highlights: Two energy-saving plans are proposed to retrofit a computer room air conditioning. Energy models of the existing cooling system and retrofit plans are established. Among these retrofit plans, the loop thermosyphon system has the best performance.